Zoobreak eaudiobook - Korman, Gordon (Swindle, 2009)
Award-winning author Gordon Korman has sold millions of copies of his books worldwide and has captivated young readers everywhere with his distinct brand of laugh-out-loud humor. Zoobreak revisits the characters from Korman' s popular Swindle, as Griffin Bing and his friends come together for another heist. Savannah' s pet monkey has been kidnapped and given to a zoo! Griffin quickly puts together a plan to steal the critter back, but not all goes smoothly. The crew realizes animals in the zoo are treated badly, so they hatch another scheme— to smuggle the animals into a better zoo.